Politeness Strategies in the Dialogue of Dilan 1990: A Pragmatic Approach - Novita Aulia; Roma Ito Br Pane; Rica Octaviani Sihotang (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study is motivated by the importance of politeness strategies in film discourse as a reflection of social interaction and cultural values. It aims to identify the types of politeness strategies used in the film Dilan 1990 and to determine the most dominant strategy along with its contextual use in interpersonal interactions, based on Brown and Levinson’s framework. Employing a descriptive qualitative method, the data consist of 40 utterances containing potential face-threatening acts. The data were analyzed through identification, classification, and interpretation according to four politeness strategies: Bald on Record, Positive Politeness, Negative Politeness, and Off-Record. The findings reveal that all four strategies appear in the film dialogues, with Positive Politeness as the dominant strategy, indicating closeness, humor, and social solidarity, particularly between the main characters, Dilan and Milea. Bald on Record is mainly used in instructional and hierarchical relationships, while Negative Politeness and Off-Record occur in more sensitive situations or when indirect meanings are intended. These results imply that Dilan 1990 represents politeness values within Indonesia’s collectivistic culture, especially in youth communication that emphasizes harmony and social cohesion.